After the War Nation-Building from FDR to George W. Bush - Dobbins, James (RAND Corporation, 2008)
From the post-World War II era through the Cold War, post-Cold War era, and current war on terrorism, this volume assesses how U.S. presidential decisionmaking style and administrative structure can work in favor of, as well as against, the nation-building goals of the U.S. government and military and those of its coalition partners and allies.